2020
DOI: 10.1186/s12885-020-07220-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of relapse in stage I testicular germ cell tumor patients on surveillance: investigation of biomarkers

Abstract: Background: Better biomarkers for assessing risk of relapse in stage I testicular germ cell tumor patients are needed, to complement classical histopathological variables. We aimed to assess the prognostic value of previously suggested biomarkers, related to proliferation (MIB-1 and TEX19) and to immune microenvironment (CXCL12, CXCR4, beta-catenin and MECA-79) in a surveillance cohort of stage I testicular germ cell tumor patients. Methods: A total of 70 patients were included. Survival analyses were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…Consequently, increased incidence of side effects has been observed (secondary neoplasms, metabolic syndrome, coronary heart disease and others) in those young patients [3]. Thus, there is a need for biomarkers that reliably stratify patients concerning the risk of relapse [4]. Additionally, there is an urgent need for novel and less toxic targeted treatment options that might allow for dose reduction of chemotherapy agents.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, increased incidence of side effects has been observed (secondary neoplasms, metabolic syndrome, coronary heart disease and others) in those young patients [3]. Thus, there is a need for biomarkers that reliably stratify patients concerning the risk of relapse [4]. Additionally, there is an urgent need for novel and less toxic targeted treatment options that might allow for dose reduction of chemotherapy agents.…”
Section: Introductionmentioning
confidence: 99%
“…Another work has shown that high β-catenin expression in primary testicular GCTs was associated with relapse and NS-GCT histology in clinical stage I disease. This finding may help refining the approach to risk stratification of stage I GCTs [ 73 ]. Western blot analysis in our GCT cell lines revealed significantly increased levels of β-catenin protein expression in two cisplatin-resistant cell lines with the exception of NTERA-2 CisR cells where the expression was significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The latter comprise a complex array of subtypes that include embryonal carcinoma (EC), choriocarcinoma (CH), yolk sac tumor (YST), and teratoma (TE) [1][2][3][4][5][6][7]. Overall, TGCTs represent a model of curable disease, with most patients presenting with stage I disease (around 70%), but approximately 75% of these are cured with orchiectomy alone, without the need for subsequent adjuvant treatments [4,8,9]. For those who require systemic therapy, TGCTs present extreme sensitivity to cisplatin-based chemotherapy, due to their unique molecular background [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…For those who require systemic therapy, TGCTs present extreme sensitivity to cisplatin-based chemotherapy, due to their unique molecular background [3,10]. However, a significant group of patients relapse, most frequently within the first two years after initial diagnosis [9,11]. Thus, inguinal orchiectomy followed by close surveillance may not be enough, implying the need for further treatments, which leads to higher morbidity [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation